Ulul Albab Perspektif Al-Qur'an (Kajian Maudlu'iy dan Integrasi Agama Dan Sains) - Firdaus, Dwi Hidayatul (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2021)
Thematic discussion about ulul albab in the Qur'an is always interesting to do because it reminds Muslims of the importance of this ulul albab figure. Because this ulul albab figure who became the world has developed in a balanced way between knowledge and worship with the concepts of tafakkur and tasyakkur. To study more deeply, the Ulul Albab study in this study was carried out using the maudhu'iy method by collecting thematic verses scattered in various letters to become more focused and systematic. The technique used is to describe thematic poems about ulul albab plus the qoul ulema of tafsir who are concerned in this study and the thoughts of Ian G Barbour in terms of the integration of religion and science. The results of the literature research conducted are that three activities, concepts, and characteristics must exist in the figure of ulul albab. Namely, main activity (main activity), object activity (activity object), and strategy of action (strategy). These three aspects must be realized in the person of Ulul Albab as a form of personal manifestation who can reflect deeply on natural and social phenomena, which encourages him to develop knowledge, based on total submission to the greatness of God, in this case, the Ulul Albab person must integrate dhikr, thought, good deeds and knowledge. Ian G Barbour stated that there is a need for a systematic synthesis in integrating religion and science in this integration process.